Characterization of Polypropylene post-consume / Banana Fiber Composites - de Leão, Ariadne Gonçalves; Pereira, Patricia Soares da Costa; Bastos, Daniele Cruz (Acta Scientiae et Technicae, 2018)
In this study, banana fibre surfaces were chemically modified and composites using polypropylene as a matrix were prepared. The FTIR analysis confirmed that the esterification increased the crystallinity and thermal stability of the acetylated fibres. Composites showed a decrease in the melt flow index and a slight reduction in density and hardness in relation to the matrix. Good matrix/fibre adhesion was observed by SEM micrographs.